Implementasi Kebijakan Program Pemberdayaan Organisasi Kemasyarakatan Di Provinsi Dki Jakarta - Nurhadi, Andi Ilham; Eviany, Eva; Madjid, Udaya (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
Based on data released by the Subdirectorate of Partnership and Empowerment of Mass Organizations of the Ministry of Home Affairs (2023), there are still several Mass Organizations in Gambir Village, Gambir District, Central Jakarta City, DKI Jakarta Province that have not been registered, so these Mass Organizations have not received legal entity approval and do not have SKT. (Registered Certificate) issued by the Ministry of Home Affairs and the Ministry of Law and Human Rights, as a result, the mass organization does not receive grant assistance from the government. The mass organization is the NGO Indonesian Immigration Watch (IIW) or the Indonesian Immigration Monitor and Jakarta Restoration Movement (PRAJA). The aim of this research is to: describe and analyze the implementation of Community Organization empowerment program policies in DKI Jakarta Province. In this research, researchers used a qualitative research design with descriptive methods and an inductive approach. The research results show that institutional capacity is strengthened, through strengthening organizational management, providing data and information, developing partnerships, supporting expertise, programs and mentoring, strengthening leadership and cadre formation, providing awards and research and development. Finally, improving the quality of human resources, through education and training, apprenticeships and/or courses. Based on the explanation above, empowerment of mass organizations is the obligation of regional governments or related agencies, in empowering mass organizations as explained in the Law governing community organizations.